Depresi pada Remaja: Gejala dan Permasalahannya - Ktut Dianovinina (Jurnal Online Psikogenesis, 2018)
Less of adolescent were able to overcome some obstacles in transitional periode, many of them experienced some unpleasant events. Lack of preparedness in dealing with various problems of life, could be a factor triggered a higher risk of depression. Depression is undetectable from its occurrence, but usually known after several problems happened, following the suicide phenomenon as the third biggest cause of adolescents death in the world. The research purposed of knowing the behavior of adolescents that occurred as the depression symptom and its problems accompanied. This study used quantitative descriptive methode. New entry college students (ages 16 -18 years) participated in data collelction. Samples were hired by using purposive sampling methode. Among 230 students who assessed with Child Depression Inventory (CDI), found 17 depression students and 65 potentially depression students that participate further in this study. The results showed, there were some behaviors reflected by its most common symptoms of depression experienced by the samples, such as consider of low in self-esteem, difficulty in concentrating, lost of interest in activity, drastic weight changes, and difficulty in sleeping through the night. Furthermore, the matters attached were mostly related to body dissatisfaction, poor learning achievement, getting unpleasant treatment from others, both friends and parents, and the relationship between parents who problematic. As the problems persisted being aware of, it is expected to make parents to be more sensitive, and recognize their adolescent behaviors that might become symptoms of depression and know the events that were at risk of causing depression.